Interest in documentary credits Preparation (Islamic Sciences Journal, 2023)
ABSTRACT       One of the graces of Allah upon the nation is that he preserves its religion and fosters its Sharia, which is the end of the Shari’as. Every one of the sons of Adam needs the other in it, whether it is selling, buying, gifting, loaning, speculating, or other financial transactions, However these transactions are marred by the imbalance and suspicion as a result of friction with financial systems, whether capitalist or socialist, they are trading in ways, some of them legitimate, others illegal, or mixed.Islam has proven its ability to manage areas of life, including the economic aspect represented in the jurisprudence of transactions, which is one of the most important fields of Islamic economics.Among the formulas developed in contemporary financial transactions are: documentary credits, The correlation of these credits with interest, is behind  the desire to discuss this aspect in this subject , i.e (benefits in documentary credits(.I ask God Almighty for success in this research, and our last prayer is that praise be to God, Lord of the worlds, and blessings and peace be upon our master Muhammad and upon all his family and companions, and peace and God's mercy and blessings be upon you.